2018
DOI: 10.1371/journal.pone.0199734
|View full text |Cite
|
Sign up to set email alerts
|

A whole-genome transcriptome analysis of articular chondrocytes in secondary osteoarthritis of the hip

Abstract: ObjectiveTo date, exhaustive gene expression analyses of chondrocytes in hip osteoarthritis (OA) have yielded specific gene expression patterns. No study has reported on the exhaustive transcriptome of secondary hip OA based on acetabular dysplasia in a Japanese population, while previous reports have focused on primary or idiopathic hip OA in Caucasian populations. This study aims to search for specific gene expression patterns of secondary hip OA chondrocytes by transcriptome analysis.DesignHuman articular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Arnold et al reported that IGFBP7 promoted osteogenesis of stem cells and may protect them from bone disease in multiple myeloma . Using protein interaction and microRNA network analyses, Wang et al reported that IGFBP7 expression was associated with the development of osteoarthritis (OA), which was confirmed by two other studies . In our previous study, we reported that IGFBP7 enhanced osteogenic differentiation of BMSCs via the Wnt/β‐catenin signalling pathway in vitro and promoted new bone formation in vivo .…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Arnold et al reported that IGFBP7 promoted osteogenesis of stem cells and may protect them from bone disease in multiple myeloma . Using protein interaction and microRNA network analyses, Wang et al reported that IGFBP7 expression was associated with the development of osteoarthritis (OA), which was confirmed by two other studies . In our previous study, we reported that IGFBP7 enhanced osteogenic differentiation of BMSCs via the Wnt/β‐catenin signalling pathway in vitro and promoted new bone formation in vivo .…”
Section: Introductionsupporting
confidence: 64%
“…IGFBP7 is methylated in subchondral bones and is related to its sclerosis . IGFBP7 is also reported to be associated with the development of OA, another bone metabolism‐related orthopaedic disease . As direct evidence, our previous study showed that IGFBP7 enhanced osteogenesis in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Notch3 is a family member of Notch receptors, and genetic deletion of Notch3 or the blockade of Notch3 signaling prevents joint damage and attenuates in ammation of in ammatory arthritis [72]. (a chloride intracellular channel protein) are reported to be highly expressed under osteoarthritic condition [86][87][88][89][90][91][92][93][94][95]. Thus, these results suggest that DAE might serve as a candidate supplement for preventing cartilage degeneration and in ammation.…”
Section: Discussionmentioning
confidence: 87%
“…Ramp3 is a receptor activitymodifying protein that is highly expressed during joint in ammation [83]. Cyp1b1 (a member of the cytochrome P450 enzyme family), Pcsk1n (an inhibitor of prohormone convertase 1), Dlx3 (a family member of homeobox proteins), Nkd2 (a regulator of in ammatory response), Mmp19 (a subtype of matrix metalloproteinases), Htra4 (a subtype of serine proteases), Aplnr (a G protein-coupled receptor of apelin), Tubb2b (a beta isoform of tubulin), Arg1 (a cytosolic manganese-dependent enzyme) and Clic5 (a chloride intracellular channel protein) are reported to be highly expressed under osteoarthritic condition [84][85][86][87][88][89][90][91][92][93]. Thus, these results suggest that DAE play a potential role in preventing articular cartilage degeneration and in ammation by inhibiting multiple genes involved in the pathophysiology of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%